1990
DOI: 10.1002/eji.1830200922
|View full text |Cite
|
Sign up to set email alerts
|

Functional markers of the major histocompatibility gene complex of snakes

Abstract: In optimal seasonal conditions, outbred adult snakes Psammophis sibilans displayed the major immunological functions related, in mammals, to the presence of the major histocompatibility gene complex (MHC). Thus, out of 30 snake random pairs that exchanged skin transplants 72.9% rejected their allograft in an acute or subacute manner. Strongly significant proliferative response was recorded in 67.3% of 168 separate one-way mixed leukocyte reaction (MLR) cultures. Lymphocytes from 6/11 snakes immunized by skin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…This may have occurred because as seasonal conditions changed, they did not allow for the rejection to occur completely before the onset of winter. Farag and El Ridi found that, like other vertebrates, tissue rejection in reptiles is dependent on the major histocompatibility gene complex (MHC) (Farag and El Ridi, 1990).…”
Section: Cell-mediated Immunitymentioning
confidence: 99%
“…This may have occurred because as seasonal conditions changed, they did not allow for the rejection to occur completely before the onset of winter. Farag and El Ridi found that, like other vertebrates, tissue rejection in reptiles is dependent on the major histocompatibility gene complex (MHC) (Farag and El Ridi, 1990).…”
Section: Cell-mediated Immunitymentioning
confidence: 99%